Electroanatomic substrate of atrial fibrillation in patients after COVID-19 - An. M. Osadchy; V. V. Semenyuta; A. V. Kamenev; S. G. Shcherbak; D. S. Lebedev (Российский кардиологический журнал, 2021)
Aim. To determine the features of left atrial electroanatomic structure and the arrhythmia substrate in patients with atrial fibrillation (AF) after coronavirus disease 2019 (COVID-19).Material and methods. The pilot study included 20 patients with AF who underwent catheter radiofrequency ablation. Ten patients had COVID-19 and 10 patients were included as a control group. AF substrate was identified using anatomic and bipolar mapping. Zones with following amplitudes were analyzed: <0,25 mV, <0,5 mV, from 0,5 to 0,75 mV inclusive, and >0,75 mV. Left atrial volume was determined based on anatomic map.Results. The groups were homogeneous in AF type, number of patients after prior pulmonary vein isolation, and heart rate during mapping. In the COVID-19 group, there was a higher area of fibrous zones with an amplitude of <0,25 mV (51,5±16,6% vs 29,1±16,1% in the control group, p=0,007), <0,5 mV (76,7±11,5% vs 45,6±22,7% in the control group, p=0,001) and a lower area of intact myocardium with an amplitude >0,75 mV (11,6±8,0% vs 45,0±25,0% in the control group, p=0,001). In 7 COVID-19 patients, the posterior wall was isolated due to low-amplitude zones. Of these, three patients underwent surgery for the first time. According to ROC analysis, in patients after COVID-19, fibrous tissue (<0,5 mV) occupies more than half of the area, while normal tissue (>0,75 mV) — ~30% or less.Conclusion. This study shows that SARS-CoV-2 infection may cause left atrial remodeling in the form of diffuse fibrosis. The arrhythmia substrate in patients after COVID-19 can be localized not only in pulmonary vein mouths, but also in other left atrial areas. This must be taken into account before ablation, even if the procedure is being performed for the first time. It is recommended to perform amplitude mapping for all patients who have had SARS-CoV-2 infection in order to identify fibrous zones and plan the operation extent.